Vegetation cover of riparian and coastal zones of forest swamps in the Slobozhansky National Nature Park (structural features and direction of transformation) - Bezrodnova, O.; KlieshchА. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
This article is devoted to study the characteristics of ecological-cenotic structure and directions of vegetation cover transformations in riparian and coastal zones of forest swamps within the forest-steppe zone (north-western part of Kharkiv Oblast, Ukraine). The survey has been conducted in 2013–2018 in the territory of the Slobozhansky National Natural Park. Plant communities were surveyed both in phanerophyte and grass biotopes types, having different genesis and degree of disturbance (from terrestrial to aquatic, from native to artificially created forest plantations). A number of regionally rare plant species were identified in their composition (Dryopteris carthusiana (Vill.) H.P.Fuchs, Majanthemum bifolium (L.) F.W.Schmidt, Calluna vulgaris (L.) Hull, Equisetum sylvaticum L., Potentilla erecta (L.) Raeusch., Rubus saxatilis L., Eriophorum angustifolium Honck., E. vaginatum L., Drosera rotundifolia L., Nymphaea candida C.Presl, Utricularia vulgaris L.) and U. minor L. – a species listed in the Red Book of Ukraine. Route and stationary techniques of field surveys were used for clarification the general features of horizontal vegetation structural organization, as well as for studying the effect of environmental factors on state and stability of plant communities. Usage of mobile GIS applications in geodata collection and their further processing in ArcMap project allowed us to develop a large-scale geobotanical map (1:1500) as an area of permanent botanical survey (1.9 ha). According to the results of phytoindication, indicators of 7 environmental edaphotop regimes in 25 plant communities studied (objects of mapping and further monitoring) have been identified. Based on the geobotanical map, integration of data on the intensity of vegetation transformation have been conducted. It was found that plant communities ІV (the highest) and III degrees of transformation cover an area more than 0.6 hectares (one third of the total plot area). These communities were occurred mainly in phanerophyte-type biotopes (aspen, willow, birch, and, partly, pine), which have been affected by pyrogenic and biogenic factors. The GIS-project created as a result of the study serves as a geo-information base that can be further improved and used to solve other applied problems.